ANTIOXIDANT POTENTIAL OF CLITORIA TERNATEA LEAF EXTRACTS IN VITRO - A.JAYACHITRA; P.R. PADMA (International Journal of Pharma and Bio Sciences, 2012)
Enzymic antioxidants were analyzed in both blue flowered leaf and white flowered leaf of Clitoria ternatea. The in vitro model used in the study as alternatives to live animals, was goat liver slices. The liver slices exposed to different treatments were incubated for one hour at 37ËšC with very mild shaking. The enzymic antioxidant activity was analyzed by using goat liver slices, both blue flowered leaf and white flowered leaf of Clitoria ternatea and H2O2 as oxidant. The results showed that the white flowered leaves had higher content of all the enzymic antioxidants analyzed than the blue flower.